2015
DOI: 10.3390/jfb6010143
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Implant Surface Topography on Primary Stability in a Standardized Osteoporosis Rabbit Model Study

Abstract: Evaluating primary stability is important to predict the prognosis of dental implant treatment. Primary stability is decreased in a low bone density site such as osteoporosis. However, it is difficult to apply in small animal and the effect of the different implant surface topography for the primary stability at low bone density site has not yet fully been investigated. The purpose of the present study was to evaluate the influence of implant surface topography on primary stability in a standardized osteoporos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
(22 reference statements)
0
18
0
2
Order By: Relevance
“…; Oue et al. ). ISQ value of the glucocorticoid‐induced osteoporotic animals was lower than normal at the installation in the distal epiphysis of the rabbit femur (Oue et al.…”
Section: Discussionmentioning
confidence: 96%
“…; Oue et al. ). ISQ value of the glucocorticoid‐induced osteoporotic animals was lower than normal at the installation in the distal epiphysis of the rabbit femur (Oue et al.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, in terms of mechanical strength analysis, our previous study showed that the maximum mechanical bone strength in the bonereduced rabbit model was lower than that in a normal rabbit model. Therefore, the glucocorticoid-induced model showed a greater reduction of bone density and mechanical strength of femoral cortical bone (16). Intermittent PTH administration affects bone quality by promoting preosteoblastic proliferation and osteoblast bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study of primary stability demonstrated that the IT and ISQ values were significantly lower in the osteoporosis rabbit model than in the untreated rabbit model. Furthermore, a previous evaluation of tibial bone mechanical strength by the 3-point bending test indicated that bone strength in animals with osteoporosis was significantly lower than that in normal animals (16).…”
Section: Discussionmentioning
confidence: 99%
“…The screw‐type implant aids in the easy acquisition of primary stability. Moreover, implant surface topography is a key factor in achieving osseointegration . The most common modification of implant topography is surface roughness, which can be achieved by acid etching, sandblasting or oxidization .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, implant surface topography is a key factor in achieving osseointegration . The most common modification of implant topography is surface roughness, which can be achieved by acid etching, sandblasting or oxidization . Among the different surface‐treatment techniques, the use of a resorbable blasting medium (RBM) is a classic subtractive technique that is used for dental implant surfaces .…”
Section: Introductionmentioning
confidence: 99%